Extracellular Matrix From Hypertrophic Myocardium Provokes Impaired Twitch Dynamics in Healthy Cardiomyocytes - Lorenzo R. Sewanan, MS; Jonas Schwan, PhD; Jonathan Kluger, BSE; Jinkyu Park, PhD; Daniel L. Jacoby, MD; Yibing Qyang, PhD; Stuart G. Campbell, PhD (JACC: Basic to Translational Science, 2019)
Summary: Hypertrophic cardiomyopathy (HCM) is often caused by single sarcomeric gene mutations that affect muscle contraction. Pharmacological correction of mutation effects prevents but does not reverse disease in mouse models. Suspecting that diseased extracellular matrix is to blame, we obtained myocardium from a miniature swine model of HCM, decellularized thin slices of the tissue, and re-seeded them with healthy human induced pluripotent stem cell–derived cardiomyocytes. Compared with cardiomyocytes grown on healthy extracellular matrix, those grown on the diseased matrix exhibited prolonged contractions and poor relaxation. This outcome suggests that extracellular matrix abnormalities must be addressed in therapies targeting established HCM. Key Words: diastolic dysfunction, engineered heart tissue, fibrosis, hypertrophic cardiomyopathy, iPSC-derived cardiomyocyte, MYH7 mutation